KOMUNIKASI IJIC: PROFESIONALISME SEBAGAI MODAL AKREDITASI JURNAL - gunawan gunawan (Indonesian Journal of Islamic Communication, 2019)
In today's digital era, publication of scientific works is a standard for the progress of universities and even the State. Publication of articles in journals both nationally and internationally is a standard for the development of science and technology which is loved by many people including Indonesians. Therefore, IJIC is present as a scientific journal to contest in the standard of higher education progress. To support the management of online journal system journals and arouse the spirit of writing scientific articles, IJIC held a workshop on reputable article writing techniques and management of Online Journal System journal management, by presenting two reliable resource persons namely Al Khanif, SH, MA, Ph.D as Editor in Chief Journal Of Southeast Asian Human Rights and Director of the center for human rights, multiculturalism and migration (CHRM2) Chair Persons of the Indonesian Consortium for Human Rights Lectures, SEPAHAM Indonesia and Dr. Abdul Muhid, M.Sc as Editor In Chief Engagement: Journal of Community Service Kopertais Region IV Surabaya that has been accredited by Sprott 3. ID Scopus 57209454955. The results obtained from the workshop were at least three things namely First; the author is a writer who studies deeply, is written and then published. Second; the writing style of the IJIC article is seven in general namely the title. Ownership lines (byline), Abstracts, Keywords (keywords), Body of writing, references, and completeness of articles. Third; the editorial board of IJIC has an extraordinary passion for serving science, even though it is not supported by various things such as facilities and finance. Even though the journal management agency must have the ability to organize journal publishing. This is based because the institution must have the capital to publish a journal and have an IP address network device and have an online journal publishing information system or better known as an online journal system (OJS).